2015
DOI: 10.1002/ana.24394
|View full text |Cite
|
Sign up to set email alerts
|

Fyn inhibition rescues established memory and synapse loss in Alzheimer mice

Abstract: Objective Currently no effective disease modifying agents exist for the treatment of AD. The Fyn tyrosine kinase is implicated in Alzheimer’s disease (AD) pathology triggered by amyloid-β oligomers (Aβo) and propagated by Tau. Thus, Fyn inhibition may prevent or delay disease progression. Here, we sought to repurpose the Src family kinase inhibitor oncology compound, AZD0530, for AD. Methods The pharmacokinetics and distribution of AZD0530 were evaluated in mice. Inhibition of Aβo signaling to Fyn, Pyk2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
294
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 286 publications
(315 citation statements)
references
References 59 publications
(190 reference statements)
7
294
0
Order By: Relevance
“…Pyk2 and CamKII are two kinases associated with the PrP C -mGluR5 complex that are activated by acute A␤o stimulation in a PrP C -and mGluR5-dependent manner (16,18). Here we determined that DHPG as well as ionomycin treatments activate both kinases similarly to A␤o-triggered phosphorylation of Pyk2 and CamKII (Fig.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Pyk2 and CamKII are two kinases associated with the PrP C -mGluR5 complex that are activated by acute A␤o stimulation in a PrP C -and mGluR5-dependent manner (16,18). Here we determined that DHPG as well as ionomycin treatments activate both kinases similarly to A␤o-triggered phosphorylation of Pyk2 and CamKII (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…A␤o binding to PrP C triggers intracellular signaling via metabotropic glutamate receptor 5 (mGluR5) (12,16,17), which includes downstream Fyn activation and synapse loss (12,13,18). We recently demonstrated that PrP C is linked to intracellular proteins via mGluR5 and that this coupling is modulated by extracellular A␤o (16).…”
mentioning
confidence: 99%
“…Figure 2 depicts a brief synthesis scheme for the preparation of the unlabeled UCB-J reference standard (3), the trifluoroborate radiolabeling precursor (6), and the radiolabeled tracer (7). Both the precursor and the reference standard were prepared from commercially available or custom-synthesized starting materials.…”
Section: Chemistrymentioning
confidence: 99%
“…Mice deficient in SV2A develop seizures and die within 3 wk of birth (4). In addition to its well-established role as the target for the antiepileptic drug levetiracetam (5,6), dysfunction of SV2A has been implicated in other neurologic disorders such as Alzheimer's disease (7)(8)(9).…”
mentioning
confidence: 99%
“…AstraZeneca are also collaborating with Yale University to repurpose saracatinib (AZD0530), a Src tyrosine kinase inhibitor, as a treatment for AD, on the basis of its Fyn kinase inhibitory properties [50]. A phase 1b trial in AD patients has been successful and a phase IIa study is underway [51].…”
Section: New Approaches and The Future Of Academic Drug Discoverymentioning
confidence: 99%